Hubungan Antara Jenis Komunikasi Dan Gaya Asuhan Ibu Bapa Terhadap Tingkah Laku Devian Remaja: Kajian Literatur (Relationship Between The Type Of Communication And Parenting Style Towards Teen Deviant Behaviour: A Literature Review) - Mohammad Rawi, Ali Hafizar; Abdullah, Norida; Shamshul Al Kamal, Siti Nurul Suhada (Penerbit Universiti, UTeM, 2017)
This research is intended at looking into how far parent’s communication and parenting style will affect children’s deviant behaviour among teenagers who has criminal records in few districts, in the state of Pahang. Samples involved 150 teenagers who are chosen using purposive sampling from an Interactive Workshop that have been identified and organized by Welfare Department in Pahang. Research instrument used in the study is survey which intends at measuring communication level, parenting style, teenager’s risk level. The instruments are Family Communication Patterns Instruments by Ritchie and Fitzpatrick 1990 which has the reliability coefficient of 0.75, Parent’s Parenting Style Towards Teenagers Instrument (adapted from Paulson’s Perception of Parenting Scale 1994) with reliability coefficient of 0.614 and Teenager’s Deviant Behaviour Instrument (Translated from Junger’s Delinquency Survey 1997) with the reliability coefficient of 0.923 based on previous surveys. Descriptive analysis will be used to analyse frequency, mean and standard deviation. T-test however will be used to test the difference in terms of gender and teenager’s deviant behaviour. On the other hand, Pearson correlation coefficient is used to measure relation between parenting style and teenager’s deviant behaviour.